1997
DOI: 10.1007/pl00005773
|View full text |Cite
|
Sign up to set email alerts
|

Responses of tonically discharging neurons in the monkey striatum to primary rewards delivered during different behavioral states

Abstract: In the primate striatum, the tonically discharging neurons respond to conditioned stimuli associated with reward. We investigated whether these neurons respond to the reward itself and how changes in the behavioral context in which the reward is delivered might influence their responsiveness. A total of 286 neurons in the caudate nucleus and putamen were studied in two awake macaque monkeys while liquid reward was delivered in three behavioral situations: (1) an instrumental task, in which reward was delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
137
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(154 citation statements)
references
References 32 publications
17
137
0
Order By: Relevance
“…Moreover, Apicella and colleagues (1991) found that the activity of TANs within the striatum changed during a delayed go/no-go task that demands flexible responding for goal-directed behavior. TANs also exhibited changes in activity when either the timing of a predictive cue is changed or the timing of reward delivery (Apicella, Legallet & Trouche, 1997;Ravel et al, 2001). This change in TANs activity with a switch in conditions may facilitate one's ability to adapt to changing environmental conditions in order to achieve a goal.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Apicella and colleagues (1991) found that the activity of TANs within the striatum changed during a delayed go/no-go task that demands flexible responding for goal-directed behavior. TANs also exhibited changes in activity when either the timing of a predictive cue is changed or the timing of reward delivery (Apicella, Legallet & Trouche, 1997;Ravel et al, 2001). This change in TANs activity with a switch in conditions may facilitate one's ability to adapt to changing environmental conditions in order to achieve a goal.…”
Section: Discussionmentioning
confidence: 99%
“…The task relationships of neuronal discharges were assessed on-line in the form of rasters aligned on each task event. We used well established criteria to identify TANs (Aosaki et al, 1994;Apicella et al, 1997). Every TAN isolated was examined while the monkey performed the task with reward at p ϭ 1.0.…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated TAN responsiveness to task events in terms of changes in firing detected on the basis of a Wilcoxon signed-rank test (Apicella et al, 1997) and only neurons with statistically significant changes against control activity were considered responsive. The baseline activity was calculated during the 0.5 s before the presentation of the trigger stimulus.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, these interneurons appear highly responsive to stimulus detection, movement control, and context recognition. Thus, while TANs are somewhat responsive to the experience of rewards, they exhibit a significantly greater response to contextual features (cues) associated with the reward (Aosaki et al, 1994;Apicella et al, 1997;Kimura et al, 2003). This feature distinguishes the TANs from mesostriatal DANs, which are equally responsive to both rewards and their associated cues.…”
Section: Mesostriatal Cholinergic Neuronsmentioning
confidence: 98%